2019
DOI: 10.17582/journal.aavs/2019/7.s2.51.56
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Listeria Monocytogenes Isolated from Different Animal-Origin Food Items from Urban and Rural Areas

Abstract: | Listeriosis is classified as the third main cause of food-borne diseases and it is one of the significant bacterial zoonotic infections causing high fatality rates worldwide. The aim of this research was to isolate and characterize Listeria monocytogenes (L. monocytogenes) from different food items in Sharkia Province, Egypt. A total of 200 food samples were collected aseptically from local markets and subjected to the phenotypic and genotypic characterization of L. monocytogenes. Listeria species were isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 0 publications
3
6
0
Order By: Relevance
“…The presence of the hlyA gene in all strains examined for our study's virulotyping analysis was consistent with research by Osman et al (2016), Şanlıbaba et al (2018), Owusu-Kwarteng et al (2018), El-Demerdash et al (2019 and Skowron et al (2019). Additionally, it was found that L. monocytogenes' ability to form biofilms is impacted by the presence of the hlyA virulence gene (Price et al, 2018), as this organism is better able to withstand ineffective disinfection during cleaning procedures, which results in the continued presence of L. monocytogenes in the final product.…”
Section: Discussionsupporting
confidence: 87%
“…The presence of the hlyA gene in all strains examined for our study's virulotyping analysis was consistent with research by Osman et al (2016), Şanlıbaba et al (2018), Owusu-Kwarteng et al (2018), El-Demerdash et al (2019 and Skowron et al (2019). Additionally, it was found that L. monocytogenes' ability to form biofilms is impacted by the presence of the hlyA virulence gene (Price et al, 2018), as this organism is better able to withstand ineffective disinfection during cleaning procedures, which results in the continued presence of L. monocytogenes in the final product.…”
Section: Discussionsupporting
confidence: 87%
“…Elskens et al. (2012) proposed a general modeling framework based on the first and second migration values to predict the third migration results of SR samples. The main factors influencing the migration of cyclic siloxane oligomers from SR to food simulants are temperature, time, and the type of food simulant (i.e., n ‐hexane, n ‐heptane, and ethanol).…”
Section: Chemical Substances In Silicone Rubber and Their Migrationmentioning
confidence: 99%
“…Listeriosis is the third leading cause of foodborne disease and one of the major zoonotic bacterial infections that cause high mortality worldwide. Listeria monocytogenes is the most common cause of listeriosis in humans and animals, owing to food and environmental pollution; it has a low incidence but a high case fatality rate (El‐Demerdash & Raslan, 2019; Sołtysiuk et al., 2022). L. monocytogenes has the ability to adhere to FCMs (Casarin et al., 2016; Gram et al., 2007; Iacumin et al., 2016).…”
Section: Bacterial Biofilm On the Surface Of Srmentioning
confidence: 99%
See 1 more Smart Citation
“…Listeriosis is the main food-borne zoonotic illness because 99% of human infections are resulted from eating food products contaminated with mainly L. monocytogenes [2]. It is a Gram-positive, rod-shaped, motile, and non-spore-forming bacterium [3] and is primarily known as a veterinary pathogen, which causes basilar meningitis (circling disease) and abortion in sheep and cattle [4].…”
Section: Introductionmentioning
confidence: 99%